Kontribusi K.H. ZUbair Umar dalam Kitab al-Khulasah al-Wafiah pada Perkmbangan Falak di Indonesia - Arfah, Ahmad Tahsisul; Syarif, Muh. Rasywan (Universitas Islam Negeri Alauddin Makassar, 2024)
The The development of astronomy in Indonesia has a long history, although the study of astronomy remains limited and rare due to its complex calculations. This development is tied to the journeys of Nusantara figures to the Middle East, such as K.H. Zubair Umar, author of al-Khulasah al-Wafiah. This research focuses on his contribution to the advancement of astronomy in Indonesia through his book. This is important as astronomy affects the qibla direction and prayer times for Muslims. To address this issue, the author adopts a multidisciplinary approach. This qualitative literature research collects data from relevant sources. K.H. Zubair Umar's classic book, al-Khulasah al-Wafiah, had a significant influence in Indonesia during the Japanese occupation and early independence, used in judicial institutions and time calculations. Zubair Umar's contribution is evident through his students who became astronomy experts in Indonesia. This study promotes a deeper understanding of Islamic intellectual heritage, the history of astronomy, and appreciation for Muslim scholars' contributions. It is hoped that this research will inspire further studies on Islamic intellectualism and the history of astronomy in Indonesia.